Behavior of reinforced concrete eccentric and concentric beam-column joints under cyclic loading - Zhou, Hua. (2008)
This research was intended to investigate the behavior of reinforced concrete beam-column joints under cyclic loading. In consisted three parts. One part was an experimental study of interior eccentric beam-column joints, the second part was a parametric study of interior and exterior beam-column joints, and the last part was a numerical analysis of the effect of bond deterioration on the behavior of interior beam-column joints.